Pengaruh Rotasi Tanaman Terhadap Kesuburan Tanah dan Pengendalian Hama - Oferlina Harefa; David Trisman Jaya Zega; Niatman Harefa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Crop rotation is one of the most effective agricultural and has significant benefits in improving soil fertility, assessing health and disease, and increasing the efficiency of natural resource utilization. Agricultural strategies that have important benefits in improving soil fertility, assessing health and disease, and increasing the efficiency of natural resource utilization. To maximize nutrient utilization and reduce the risk of certain pests associated with a crop, this practice involves reducing the types of crops grown on the same land in the relevant cycle. To maximize nutrient utilization and reduce the risk of certain pests associated with a crop, this practice involves reducing the types of crops grown on the same land in the relevant cycle. In addition, crop rotation helps improve soil structure, increase cation exchange capacity (CEC), and reduce dependence on chemicals and pests. The study employed a library analysis method by reviewing several previous studies on the impact of crop rotation on agricultural productivity and soil ecology. The results showed that crop rotation can increase nitrogen levels in the soil by up to 20%, reduce pesticide use by up to 50%, and increase air use efficiency, especially in areas with limited air supply. In addition, this practice helps create a more stable agricultural ecosystem by increasing biodiversity, such as reducing the number of natural enemies of pests. The findings of this study indicate that crop rotation is a practice that not only increases crop yields but also strengthens the principle of sustainability. With proper maintenance, crop rotation can be an effective solution to reduce land degradation, improve food security, and improve ecological balance in modern food systems. resilience, and improve ecological balance in modern agricultural systems.